2005
DOI: 10.1080/10473289.2005.10464721
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Nitrate Measurement Using Nylon Filters

Abstract: Nylon filters are a popular medium to collect atmospheric fine particles in different aerosol monitoring networks, including those operated by the U.S. Environmental Protection Agency and the Interagency Monitoring of Protected Visual Environments (IMPROVE) program. Extraction of the filters by deionized water or by a basic aqueous solution (typically a mixture of sodium carbonate and sodium bicarbonate) is often performed to permit measurement of the inorganic ion content of the collected particles. Whereas p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 49 publications
1
48
2
Order By: Relevance
“…Several field experiments were designed and conducted to investigate the chemical composition of PM 2.5 aerosol and the concentrations of trace gases (HNO 3 , NH 3 and SO 2 ) at monitoring locations for the IMPROVE program from the late 1990's through 2010 ( Aerosol composition measured at these sites has previously been reported (Yu et al, 2005b(Yu et al, , 2006Lee et al, 2004Lee et al, , 2008a. In addition, a series of yearlong intensive measurements were made in Rocky Mountain National Park (November 2008-October 2009, daily), Boulder, WY (December 2006-December 2010, 3 and 4-day average), and Brush and Loveland, CO (December 2008-November 2009.…”
Section: In Situ Measurementsmentioning
confidence: 99%
“…Several field experiments were designed and conducted to investigate the chemical composition of PM 2.5 aerosol and the concentrations of trace gases (HNO 3 , NH 3 and SO 2 ) at monitoring locations for the IMPROVE program from the late 1990's through 2010 ( Aerosol composition measured at these sites has previously been reported (Yu et al, 2005b(Yu et al, , 2006Lee et al, 2004Lee et al, , 2008a. In addition, a series of yearlong intensive measurements were made in Rocky Mountain National Park (November 2008-October 2009, daily), Boulder, WY (December 2006-December 2010, 3 and 4-day average), and Brush and Loveland, CO (December 2008-November 2009.…”
Section: In Situ Measurementsmentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49][50][51][52][53] Turpin and Lim 41 concluded that a factor of about 1.6 would be appropriate for an urban organic aerosol, whereas a factor of 2.1 may be more appropriate for an aged, nonurban aerosol.…”
Section: Comparison Of Reconstructed To Measured Massmentioning
confidence: 99%
“…Collection of the aerosol usually occurs onto low cost and flexible filter packs; or using an impactor; but the time resolution and sometimes the sensitivity can be relatively poor (Huang et al 2004). In addition, the filters are not expected to retain all of the semi-volatile compounds such as ammonium nitrate (Yu et al 2005(Yu et al , 2006. The positive artifact of ammonium resulting from the adsorption and absorption of ammonia gas onto the filter or collected aerosol can not be neglected on the filter based-samples (Andersen and Hovmand 1994;Harrison and Kitto 1990;Pathak and Chan 2005).…”
Section: Introductionmentioning
confidence: 99%